2020
DOI: 10.2147/ppa.s285905
|View full text |Cite
|
Sign up to set email alerts
|

The Added Value of a Behavioral Medicine Intervention in Physiotherapy on Adherence and Physical Fitness in Exercise-Based Cardiac Rehabilitation (ECRA): A Randomised, Controlled Trial

Abstract: Purpose Despite beneficial effects, adherence to exercise-based cardiac rehabilitation (exCR) is low in patients with coronary artery disease (CAD). The aim of this study was to investigate adherence to and the effects of a behavioral medicine intervention in physiotherapy (BMIP) added to routine exCR care on the primary outcome of physical fitness compared with routine exCR care. Patients and Methods In a randomized, controlled trial, 170 patients with CAD (136 men), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…While supervised aerobic exercise programmes have been associated with reductions in blood pressure following a TIA [ 9 ], such interventions are relatively time and resource intensive, and may not be feasible or cost effective in current healthcare system settings. Poor uptake and attendance, particularly among some groups, including older adults, can also limit their efficacy [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…While supervised aerobic exercise programmes have been associated with reductions in blood pressure following a TIA [ 9 ], such interventions are relatively time and resource intensive, and may not be feasible or cost effective in current healthcare system settings. Poor uptake and attendance, particularly among some groups, including older adults, can also limit their efficacy [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise habits and changes in peak VO 2 during and after the CR program are shown in Table 2. The number of CR attendances during the 3-month CR program was higher in women (14 [11][12][13][14][15][16][17][18][19][20][21][22][23][24] sessions vs. 10 [3-15] sessions, p = 0.00020). There was no sex difference in exercise habits that The percentage trend of the predicted peak VO 2 is shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported the influence of subjective factors on the reasons for CR non-participation 18) . Furthermore, a randomized controlled trial revealed that the addition of a behavioral medicine intervention in physiotherapy to a conventional CR program contributed to the maintenance of exercise capacity in patients with CAD 19) . Therefore, it is necessary to further examine strategies to instill exercise habits.…”
Section: Discussionmentioning
confidence: 99%